2017
DOI: 10.1159/000479359
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Missense Variant in the PVRL4 Gene Underlying Ectodermal Dysplasia-Syndactyly Syndrome in a Turkish Child

Abstract: Ectodermal dysplasia-syndactyly syndrome is a rare autosomal recessive congenital disorder caused by mutations in PVRL4 coding for nectin-4. Five different mutations in the PVRL4 gene, including 3 homozygous missense mutations, have been reported. Here, we present an unreported missense variant (c.247C>T, p.His83Tyr) in a consanguineous Turkish family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
3
9
0
Order By: Relevance
“…In addition, a family with congenital alopecia has been described [ 18 ]. Similar to previous reports, our child had widely spaced teeth with conical-shaped crowns and enamel defects [ 4 , 6 , 16 , 17 , 18 , 19 , 20 ]. Moreover, orthopantomogram showed hypodontia, which has been previously described in a single family [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In addition, a family with congenital alopecia has been described [ 18 ]. Similar to previous reports, our child had widely spaced teeth with conical-shaped crowns and enamel defects [ 4 , 6 , 16 , 17 , 18 , 19 , 20 ]. Moreover, orthopantomogram showed hypodontia, which has been previously described in a single family [ 18 ].…”
Section: Discussionsupporting
confidence: 90%
“…Her clinical presentation was unique in that she presented with minimal cutaneous syndactyly. A literature review identified three sporadic EDSS1 cases and six families with two or more affected members ( Table 1 ) [ 4 , 6 , 14 , 16 , 17 , 18 , 19 , 20 ]. The patients originated from Denmark, Turkey, Algeria, Italy, Afghanistan, Pakistan, Azad Jammu and Kashmir.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations